Prepositions and theology in the Greek New Testament : an essential reference resource for exegesis - Harris, Murray J (Grand Rapids, Mi : Zondervan, 2012)
This work summarizes and demonstrates the numerous places in the Greek New Testament where prepositions contribute significantly to the meaning of the text. --from publisher description
Introduction -- Distinctive features of prepositional usage in New Testament Greek -- Dangers to be avoided in any examination of New Testament prepositional usage -- Amphi and ana -- Anti -- Apo -- Dia -- Eis -- Ek -- En -- Epi -- Kata -- Meta -- Para -- Peri -- Pro -- Pros -- Sun -- Uper -- Upo -- Propositions with baptizo -- Prepositions with pisteuo and pistis -- "Improper" prepositions -- Notable uses of selected "improper" prepositions
Includes bibliographical references and indexes
Keywords: Bible. -- Language, style; Greek language, Biblical -- Prepositions